Different streams, different needs and impacts managing international labor migration in ASEAN - Thailand (emigration) - Chalamwong, Yongyuth (Philippine Journal of Development)
For decades, Thailand has had a strong labor market in both supplying and demanding labor resources. Since the 1970s, Thailand has sent workers to the Middle East, Japan, Taiwan, Singapore, and Malaysia, among others. Based on the Socio-Economic Survey, emigrant workers come from households with low income and wealth; therefore they are heavily indebted. It can be concluded that poverty and indebtedness are push factors that had forced the migration of Thai labor, while higher income and better lives in destination countries were pull factors.